The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/376267
|View full text |Cite
|
Sign up to set email alerts
|

Reattachment of Fractured Tooth Fragment with Fiber Post: A Case Series with 1-Year Followup

Abstract: Coronal fractures of the anterior teeth are common sequelae of dental trauma. In case of complex fractures, where the fractured segment is available and there is close approximation of the segment to the remaining tooth, root canal treatment followed by reattachment of the fractured segment with fiber post reinforcement is a feasible option. The procedure is simple and economic and needs less chair-side time as compared to many conventional methods. In addition, the procedure provides good and long-lasting est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…The case history reported here not only confirms the long-term effectiveness of the reattachment technique using fiber posts but also illustrates the effectiveness and innovativeness of attaching the fiber post without drilling a hole in the crown. Our data adds to the growing number of case reports in the literature demonstrating that reattachment of a fractured tooth fragment is effective for the treatment of a coronal fracture of anterior teeth when the fracture segment is available, [9][10][11] Sapna et al reported three cases of successful reattachment of fractured segment of maxillary anterior teeth with a 12-month follow-up period. 9 They also concluded that tooth-colored fiber post may be the best option with a number of important advantages such as esthetics, good bonding between post and cement, lower chair time, and minimal tissue removal.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The case history reported here not only confirms the long-term effectiveness of the reattachment technique using fiber posts but also illustrates the effectiveness and innovativeness of attaching the fiber post without drilling a hole in the crown. Our data adds to the growing number of case reports in the literature demonstrating that reattachment of a fractured tooth fragment is effective for the treatment of a coronal fracture of anterior teeth when the fracture segment is available, [9][10][11] Sapna et al reported three cases of successful reattachment of fractured segment of maxillary anterior teeth with a 12-month follow-up period. 9 They also concluded that tooth-colored fiber post may be the best option with a number of important advantages such as esthetics, good bonding between post and cement, lower chair time, and minimal tissue removal.…”
Section: Discussionmentioning
confidence: 70%
“…Our data adds to the growing number of case reports in the literature demonstrating that reattachment of a fractured tooth fragment is effective for the treatment of a coronal fracture of anterior teeth when the fracture segment is available, [9][10][11] Sapna et al reported three cases of successful reattachment of fractured segment of maxillary anterior teeth with a 12-month follow-up period. 9 They also concluded that tooth-colored fiber post may be the best option with a number of important advantages such as esthetics, good bonding between post and cement, lower chair time, and minimal tissue removal. 9 It appears that the use of a fiber post with fractured teeth minimizes the stress on the reattached tooth fragment as it interlocks the two fragments.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…3,7 Bu dişlerde kron-kök kırığı meydana gelmesi hâlinde, mukojinjival flep kaldırılarak gerçekleştirilen osteotomi, osteoplasti, ortodontik veya cerrahi ekstrüzyonu takiben kırılan parçanın yerine yapıştırılması, dişin kompozit rezin gibi materyallerle restorasyonu veya protetik olarak tedavi edilmesi mümkündür. 6,8,9 Kırık hattının lokalizasyonu ve kalan sağlam diş dokusu miktarı tedavi seçeneklerini belirlemektedir. 5,10 Endodontik tedavi diş kırıklarında önemli bir etkendir.…”
unclassified
“…Bir başka tedavi şekli ise; dişin kompozit rezin gibi restoratif materyal ile veya protetik olarak restore edilmesidir. 5,6 Bu çalışmada, travma sonucu kron kök kırığı oluşan üst, orta ve yan keser dişlerin multidisipliner tedavisini ve bir yıllık izlemini sunmak amaçlanmıştır. ESPE, Seefeld, Almanya) hafif basınçla kök kanallarına yerleştirildi ve yapıştırıcı siman (Elipar S10, 3M ESPE, Seefeld, Almanya) 40 sn boyunca polimerize edildi.…”
unclassified